2015
DOI: 10.1007/s12020-015-0716-5
|View full text |Cite
|
Sign up to set email alerts
|

Spindle epithelial tumor with thymus-like differentiation (SETTLE): clinical-pathological features, differential pathological diagnosis and therapy

Abstract: Spindle epithelial tumor with thymus-like differentiation (SETTLE) is a very rare tumor of the thyroid gland. An algorithm for the diagnosis and treatment of SETTLE has yet to be established. The aim of this study was to identify all case reports of SETTLE and to compare the clinical-pathological features and therapy of the cases identified. We performed a PubMed search for case reports of SETTLE in English published up to November 2014 in which "SETTLE" and "Spindle epithelial tumor with thymus-like different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…The differential diagnoses include SS, ectopic spindle cell thymoma, variants of papillary thyroid carcinoma with spindle cell component such as the cribriform‐morular variant, spindle cell variant of medullary carcinoma of thyroid, sarcomatoid anaplastic carcinoma of thyroid, and solitary fibrous tumour, most of which are easily distinguished on careful review of histology and immunohistochemistry . Ectopic cervical thymoma occurs in older patients, and is usually extra‐thyroidal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential diagnoses include SS, ectopic spindle cell thymoma, variants of papillary thyroid carcinoma with spindle cell component such as the cribriform‐morular variant, spindle cell variant of medullary carcinoma of thyroid, sarcomatoid anaplastic carcinoma of thyroid, and solitary fibrous tumour, most of which are easily distinguished on careful review of histology and immunohistochemistry . Ectopic cervical thymoma occurs in older patients, and is usually extra‐thyroidal.…”
Section: Discussionmentioning
confidence: 99%
“…However, they express CD20, and ~80% harbour GTF2I mutations, both of which were absent in our case. SS is of higher nuclear grade, lacks diffuse expression of HMWCKs/p40/p63 or SMA as in SETTLE, and harbours X:18 translocations …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients present with painless thyroid enlargement for several years prior to diagnosis. Ippolito et al recently reviewed 42 SETTLE cases and found that all patients had normal thyroid function tests and serum calcitonin and carcinoembryonic antigen levels. Radiographic imaging has not been well characterized, but a heterogeneous solid‐cystic pattern and cold thyroid scans have been reported .…”
Section: Discussionmentioning
confidence: 99%
“…Ippolito et al recently reviewed 42 SETTLE cases and found that all patients had normal thyroid function tests and serum calcitonin and carcinoembryonic antigen levels. Radiographic imaging has not been well characterized, but a heterogeneous solid‐cystic pattern and cold thyroid scans have been reported . Surgical resection (usually hemithyroidectomy) is the primary treatment; a few cases have documented good responses to chemotherapy and/or radiation.…”
Section: Discussionmentioning
confidence: 99%